1969
DOI: 10.31468/cjsdwr.36
|View full text |Cite
|
Sign up to set email alerts
|

Borrowed Voices: Conversational Storytelling in Midwifery Healthcare Visits

Abstract: Midwifery in Ontario, Canada exists at the intersection of mainstream healthcare ideology and an alternative, woman-centred ideology of care. As a result, midwifery interaction is characterized by discursive hybridity. We trace this hybridity in the conversational stories co-narrated by midwives and clients during clinic visits. We show how conversational storytelling performs a complex shifting and blending of rhetorical forms and functions integral to the clinical interaction. Conversational stories conform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…These group activities helped pregnant women bond and become friends with each other in the real life, which acted as a feeder for building a stronger community on the VBAC group. Typically, common understandings of gendered experiences also forge the relationships between mothers and their healthcare providers (McKenzie and Spoel, 2014). Our study also found that face-to-face meetings enhanced group camaraderie and trust among the members, acted as a feeder for the online community and led to fostering fluid information exchanges among members of the VBAC group.…”
Section: Response To the "How" And The "What" Questionssupporting
confidence: 53%
“…These group activities helped pregnant women bond and become friends with each other in the real life, which acted as a feeder for building a stronger community on the VBAC group. Typically, common understandings of gendered experiences also forge the relationships between mothers and their healthcare providers (McKenzie and Spoel, 2014). Our study also found that face-to-face meetings enhanced group camaraderie and trust among the members, acted as a feeder for the online community and led to fostering fluid information exchanges among members of the VBAC group.…”
Section: Response To the "How" And The "What" Questionssupporting
confidence: 53%
“…Discursive approaches to the study of information and informing have been applied within the LIS field; for example, McKenzie (2009McKenzie ( , 2010 and McKenzie and Spoel (2014) use discursive methods to examine information exchanges in midwifery care. In an interaction what comes before can be treated as a knowledge base to inform later parts of an interaction (McKenzie 2010), and groups may have shorthand references to recontextualize past stories for use in current conversations (Georgakopoulou 2007).…”
Section: Introductionmentioning
confidence: 99%